2015
DOI: 10.1186/s12885-015-1580-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnolin inhibits cell migration and invasion by targeting the ERKs/RSK2 signaling pathway

Abstract: BackgroundMagnolin is a natural compound abundantly found in Magnolia flos, which has been traditionally used in oriental medicine to treat headaches, nasal congestion and anti-inflammatory reactions. Our recent results have demonstrated that magnolin targets the active pockets of ERK1 and ERK2, which are important signaling molecules in cancer cell metastasis. The aim of this study is to evaluate the effects of magnolin on cell migration and to further explore the molecular mechanisms involved.MethodsMagnolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…To examine whether magnolin‐induced senescence is the cellular senescence or senescence‐associated secretory phenotype (SASP), we firstly examine the transactivation activity of NF‐κB, which is an important transcription factor inducing gene expression of SASP related genes . Our results demonstrated that magnolin suppressed NF‐κB transactivation activity (Figure C) as similar as our previous report . In contrast, the inhibition of NF‐κB transactivation activity was not observed in SKOV3 cells (Figure C).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…To examine whether magnolin‐induced senescence is the cellular senescence or senescence‐associated secretory phenotype (SASP), we firstly examine the transactivation activity of NF‐κB, which is an important transcription factor inducing gene expression of SASP related genes . Our results demonstrated that magnolin suppressed NF‐κB transactivation activity (Figure C) as similar as our previous report . In contrast, the inhibition of NF‐κB transactivation activity was not observed in SKOV3 cells (Figure C).…”
Section: Resultssupporting
confidence: 86%
“…21 Our results demonstrated that magnolin suppressed NF-κB transactivation activity ( Figure 4C) as similar as our previous report. 22 In contrast, the inhibition of NF-κB transactivation activity was not observed in SKOV3 cells ( Figure 4C). Moreover, magnolin did not induce or not alter the expression of IL-6, IL-8, IL-1β, MMP-1, and MMP-3 ( Figure 4D), which are well known the representative SASP markers.…”
Section: D Ovarian Cancer Cells Inhibits Cell Proliferation By Enhmentioning
confidence: 87%
“…A key signaling node induced and activated by the Her2/Mapk/Erk pathway is Rsk2 (17,18), which, in turn, promotes numerous down-stream signaling pathways associated with the development of EMT and metastasis including integrin activation, the expression of matrix metalloproteinases, the expression/activation of Creb, Stat3, cSrc, Fak, Pax, and actin polymerization (13,14,3943). Activation of these same signaling pathways is also seen in breast tumors from patients that have developed resistance to chemotherapy (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…A potential role in cell migration was first proposed when Rsk2 was found to phosphorylate the cytoskeleton-associated protein filamin A (16). Recently, Rsk2 was identified as an effector of Ras/Erk-mediated EMT and its knockdown reduces metastasis in animal models (17,18). A genome-wide mRNA analysis revealed that Erk/Rsk signaling affects the expression of over 50 genes from diverse pathways responsible for cell motility and invasiveness (19).…”
Section: Introductionmentioning
confidence: 99%
“…5A) and JB6 cells (Fig. 5D) [Cho et al, 2012;Keum et al, 2013;Yao et al, 2014;Lee et al, 2015]. However, the substrates of RSK2 which are related with COX-2 expression and histone H3 ser10 and IkBa ser32 phosphorylation are inhibited by osajin in HaCaT (Fig.…”
Section: Osajin Inhibits the Downstream Of Rsk2 Pathwaymentioning
confidence: 91%